Regulation of connexin 43-mediated gap junctional intercellular communication by Ca2+ in mouse epidermal cells is controlled by E- cadherin (The Rockefeller University Press, 1991)
Gap junctional intercellular communication (GJIC) of cultured mouse epidermal cells is mediated by a gap junction protein, connexin 43, and is dependent on the calcium concentration in the medium, with higher GJIC in a high-calcium (1.2 mM) medium. In several mouse epidermal cell lines, we found a good correlation between the level of GJIC and that of immunohistochemical staining of E-cadherin, a calcium-dependent cell adhesion molecule, at cell-cell contact areas. The variant cell line P3/22 showed both low GJIC and E-cadherin protein expression in low- and high-Ca2+ media. P3/22 cells showed very low E-cadherin mRNA expression. To test directly whether E-cadherin is involved in the Ca(2+)-dependent regulation of GJIC, we transfected the E-cadherin expression vector into P3/22 cells and obtained several stable clones which expressed high levels of E-cadherin mRNA. All transfectants expressed E-cadherin molecules at cell-cell contact areas in a calcium- dependent manner. GJIC was also observed in these transfectants and was calcium dependent. These results suggest that Ca(2+)-dependent regulation of GJIC in mouse epidermal cells is directly controlled by a calcium-dependent cell adhesion molecule, E-cadherin. Furthermore, several lines of evidence suggest that GJIC control by E-cadherin involves posttranslational regulation (assembly and/or function) of the gap junction protein connexin 43.